Metformin inhibits intracranial aneurysm formation and progression by regulating vascular smooth muscle cell phenotype switching via the AMPK/ACC pathway - Li, Sichen (J Neuroinflammation, 2020)
BACKGROUND: The regulation of vascular smooth muscle cell (VSMC) phenotype plays an important role in intracranial aneurysm (IA) formation and progression. However, the underlying mechanism remains unclear. Metformin is a 5′ AMP-activated protein kinase (AMPK) agonist that has a protective effect on vasculature. The present study investigated whether metformin modulates VSMC phenotype switching via the AMPK/acetyl-CoA carboxylase (ACC) pathway during IA pathogenesis. METHODS: Adult male Sprague-Dawley rats (n = 80) were used to establish an elastase-induced IA model. The effects of metformin on AMPK activation and VSMC phenotype modulation were examined. We also established a platelet-derived growth factor (PDGF)-BB-induced VSMC model and analyzed changes in phenotype including proliferation, migration, and apoptosis as well as AMPK/ACC axis activation under different doses of metformin, AMPK antagonist, ACC antagonist, and their combinations. RESULTS: Metformin decreased the incidence and rupture rate of IA in the rat model and induced a switch in VSMC phenotype from contractile to synthetic through activation of the AMPK/ACC pathway, as evidenced by upregulation of VSMC-specific genes and decreased levels of pro-inflammatory cytokines. AMPK/ACC axis activation inhibited the proliferation, migration, and apoptosis of VSMCs, in which phenotypic switching was induced by PDGF-BB. CONCLUSIONS: Metformin protects against IA formation and rupture by inhibiting VSMC phenotype switching and proliferation, migration, and apoptosis. Thus, metformin has therapeutic potential for the prevention of IA.